2018
DOI: 10.1186/s12916-018-1037-3
|View full text |Cite|
|
Sign up to set email alerts
|

Small contribution of gold mines to the ongoing tuberculosis epidemic in South Africa: a modeling-based study

Abstract: BackgroundGold mines represent a potential hotspot for Mycobacterium tuberculosis (Mtb) transmission and may be exacerbating the tuberculosis (TB) epidemic in South Africa. However, the presence of multiple factors complicates estimation of the mining contribution to the TB burden in South Africa.MethodsWe developed two models of TB in South Africa, a static risk model and an individual-based model that accounts for longer-term trends. Both models account for four populations — mine workers, peri-mining reside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
15
0
1
Order By: Relevance
“…However, the impact of silica exposure on miners goes beyond the workforce. A modelling study of South African gold mining communities concluded that miners and members of mining communities contributed a disproportionately large share of new tuberculosis cases nationally in relation to their proportion of the population, although the main transmission impact was local [63].…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%
“…However, the impact of silica exposure on miners goes beyond the workforce. A modelling study of South African gold mining communities concluded that miners and members of mining communities contributed a disproportionately large share of new tuberculosis cases nationally in relation to their proportion of the population, although the main transmission impact was local [63].…”
Section: Overall Completeness and Applicability Of Evidencementioning
confidence: 99%
“…88 Another modeling study in 2018 found that individual gold mine workers contribute approximately 1.6 times as many new infections compared to the general South African population. 89 However, while such disproportionate transmission was found on an individual level, the authors also found that the mining industry as a whole contributed only marginally to the overall TB epidemic in the country. Unfortunately, there is insufficient evidence to determine and quantify the contribution of former mine workers to the general TB epidemic.…”
Section: The Stabilization Of the Mining Workforcementioning
confidence: 94%
“…EMOD [41] and OpenMalaria [42]) were used in the articles modelling malaria. In the articles modelling tuberculosis, the only tool reported was EMOD [43].…”
Section: Computational Aspects and The Use Of Platformsmentioning
confidence: 99%